2007
DOI: 10.1002/ajmg.a.31578
|View full text |Cite
|
Sign up to set email alerts
|

Development of gastroschisis: Review of hypotheses, a novel hypothesis, and implications for research

Abstract: Gastroschisis, a ventral body wall defect, is a continuing challenge and concern to researchers, clinicians, and epidemiologists seeking to identify its cause(s) and pathogenesis. Concern has been renewed in recent years because, unlike most other birth defects, rates of gastroschisis are reportedly increasing in many developed and developing countries. No tenable explanation or specific causes have been identified for this trend. Rates of gastroschisis are particularly high among pregnancies of very young wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
207
1
18

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(230 citation statements)
references
References 136 publications
4
207
1
18
Order By: Relevance
“…Young maternal age is the most consistently reported risk factor (Baerg et al, 2003;Feldkamp et al, 2007;Hougland et al, 2005;Saada et al, 2005). Other maternal factors that have been suspected to increase gastroschisis risk include maternal smoking, maternal use of vasoactive substances, low socioeconomic status, low pregnancy body mass index, and Hispanic ethnicity (Haddow et al, 1993;Torfs et al, 1994;Lam et al, 1999;Werler et al, 2002;Salihu et al, 2003;Saada et al, 2005;Canfield et al, 2006;Feldkamp et al, 2007;Stothard et al, 2009). More recently, maternal birthplace (nativity) has been reported to affect the risk of congenital malformations, including gastroschisis; foreign-born women have a lower risk of delivering an infant with gastroschisis than U.S.-born women (Zhu et al, 2006;Vu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Young maternal age is the most consistently reported risk factor (Baerg et al, 2003;Feldkamp et al, 2007;Hougland et al, 2005;Saada et al, 2005). Other maternal factors that have been suspected to increase gastroschisis risk include maternal smoking, maternal use of vasoactive substances, low socioeconomic status, low pregnancy body mass index, and Hispanic ethnicity (Haddow et al, 1993;Torfs et al, 1994;Lam et al, 1999;Werler et al, 2002;Salihu et al, 2003;Saada et al, 2005;Canfield et al, 2006;Feldkamp et al, 2007;Stothard et al, 2009). More recently, maternal birthplace (nativity) has been reported to affect the risk of congenital malformations, including gastroschisis; foreign-born women have a lower risk of delivering an infant with gastroschisis than U.S.-born women (Zhu et al, 2006;Vu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…1,20 It has been reported that the incidence of gastroschisis has increased in recent years. 21 There is an increased incidence when the mother has a history of cigarette smoking, use of recreational drugs, alcohol consumption, low body mass index, increased frequency of genitourinary infection. 22,23,24 ,25,26,27 During our study period a total of 32 patients were admitted in our unit.…”
Section: Discussionmentioning
confidence: 99%
“…Эта гипотеза подтверждается тем, что гастрошизис формируется на более ранних этапах внутриутробной жизни, чем омфалоцеле. Несмотря на то что наблюдается увеличение числа новорожденных с га-строшизисом, ни один из предполагаемых тератогенных факторов (табакокурение, низкий социальный статус, мо-лодой возраст матери) не нашел подтверждения в научных исследованиях [2][3][4][5].…”
Section: хирургия 5 2016unclassified